Peran Pendidikan Kewarganegaraan Dalam Membentuk Generasi Berkarakter - Mustari, Andala (Jurnal Ilmu Pendidikan Pancasila, Kewarganegaraan, dan Hukum, 2024)
Citizenship Education (PKn) plays a strategic role in shaping young generations with strong character. Through this education, students are taught moral values, ethics, and nationalism, which serve as the foundation for building a harmonious and civilized society. Citizenship Education aims to instill a love for the homeland, legal awareness, and social responsibility. Moreover, PKn contributes to strengthening national identity and fostering a spirit of tolerance in diversity. In the modern context, this education serves as a means to face the challenges of globalization while preserving the nation's noble values. By integrating interactive and relevant learning, Citizenship Education can produce generations who are not only intellectually intelligent but also possess integrity and strong character.